EARLY POSTNATAL CORRECTION OF THE INTESTINAL MICROBIOTA AS A MAIN FACTOR OF PRIMARY PREVENTION OF ATOPY (Methodological recommendations for doctors) - Перевощикова, Нина Константиновна; Гладков, Сергей Федорович; Пичугина, Юлия Сергеевна; Суркова, Марина Александровна; Черных, Наталья Степановна (Mother and Baby in Kuzbass, 2021)
The manual reflects a modern approach to the treatment and primary prevention of atopic diseases in children and contains objective information accumulated over a long time. A conceptually new approach to modeling microsymbiocenosis in children with a hereditary predisposition to atopy, based on the use of bacteriophages, is presented. An original technique is presented that allows, in the first weeks of a child’s life, on the basis of clinical biomarkers, to carry out preventive treatment, the basis of which is the selective decontamination of representatives of opportunistic intestinal microflora, as the main factor in the realization of the atopic phenotype.